Procladius Skuse from Lake Winnipeg, Manitoba, Canada, with keys to some females and immature stages of the genus (Diptera: Chironomidae) - Sæther, Ole A. (Zootaxa, 2010)
Procladius (Holotanypus) rugulosus sp. n. from Lake Winnipeg, Manitoba, Canada, is described as male, female and pupa. Six additional species of Procladius Skuse are recorded from Lake Winnipeg of which 5 belong to the most common species in the lake. The immature stages of P. (Psilotanypus) bellus (Loew), P. (Holotanypus) culiciformis (L.), P. (H.) denticulatus Sublette, P. (H.) freemani Sublette, and P. (H.) sublettei Roback are redescribed. Species keys are given to sufficiently known Nearctic females, to pupae of Lake Winnipeg, and to Nearctic larvae of Procladius. The distribution of Procladius in Lake Winnipeg is mapped and discussed. The separation of larval instars is shown approximately to follow Dyar’s rule.